A Biophysical Evaluation of a MSW-to-energy System - Almeida, C. M. V. B.; Bonilla, S. H.; Giannetti, B. F.; Frimaio, G. S.; da Silva, C. C. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
A biophysical understanding of the MSW-to-energy facility located at the Sao Joao landfill in São Paulo is performed using emergy synthesis. The implementation of a plan for environmental compensation in fulfillment of State's requirements was also assessed. Emergy based indices are calculated to assess the environmental pressure and sustainability status of the biogas project. The study was conducted by combining the study of emergy indicators and the net emergy yield ratio to determine long-term sustainability and measure global environmental stress. The Emergy investment to the use of biogas is relatively low and profitable. The implementation of the project for environmental compensation does not change the Emergy investment significantly, but the energy recovery is high. The conclusions justify the effort invested in developing MSW-to-energy plants and are applicable for policy makers in a highly sensitive sector to achieve sustainability goals - recovery of energy.
Keywords: electricity production; emergy; MSW; compensation